Germs in the Family: The Short- and Long-Term Consequences of Intra-Household Disease Spread - N. Meltem Daysal; Hui Ding; Maya Rossin-Slater; Hannes Schwandt (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Preschool-aged children get sick frequently and spread disease to other family members. Despite the universality of this experience, there is limited causal evidence on the magnitudes and consequences of these externalities, especially for infant siblings with developing immune systems and brains. We use Danish administrative data to document that, before age one, younger siblings have 2-3 times higher hospitalization rates for respiratory conditions than older siblings. We combine birth order and within-municipality variation in respiratory disease prevalence among young children, and find lasting differential impacts of early-life respiratory disease exposure on younger siblings' earnings, educational attainment, chronic respiratory health and mental health-related outcomes.
Keywords: I12; I18; J12; J13; 330; children; early-life conditions; human capital; earnings; birth order; infectious disease